Guess Who’s Coming to Dinner? Cooking Practices at Arslantepe (Eastern Turkey) from 4200 to 2000 B.C. - Balossi Restelli, Francesca; D'Anna, Maria Bianca; Piccione, Paola (Istanbuler Mitteilungen, 2024)
Cooking practices are analyzed throughout the Late Chalcolithic and Early Bronze Age occupation at the site of Arslantepe (Malatya), in Eastern Anatolia, by investigating 347 whole cooking pots and a series of in situ but fragmented ones. These vessels are mostly found within domestic or public buildings and are thus considered to be primary indicators of the cooking practices of their inhabitants. Shape, dimensions, use wear traces, capacity and distribution are evaluated and compared; these suggest long lasting food related behaviors and practices of food manipulation that appear to characterize the subsequent cultures that developed at the site. These traditions survive changes in the shapes and positions of hearths used for cooking, and stress a modifi cation in the visibility of and social involvement in domestic food preparation. Sets of cooking devices are evaluated to identify daily and ordinary food preparation, whilst the contextualization of oversized and particular vessels testifi es extra-ordinary preparations.